PERLINDUNGAN HUKUM BAGI KREDITUR MELALUI PERJANJIAN JAMINAN FIDUSIA - Ahyani, Sri (Sekolah Tinggi Hukum Bandung, 2011)
Legal protection for creditors in an agreement on fiduciary making Ata was born on fiduciary assignment made by a notary, and continues to be clarified with the registration of deed of agreement, UUJF has been attempted to provide a technical protection of the interests of creditors, the only pity is not applied with the system asserts concretes, in a system of protection through the implementation of the execution of fiduciary security, which ultimately provides options for creditors to pursue the way of peace, which means anadditional cost, and to give appreciation is bad and not related to a maximum of legal protection for creditors.Keywords: Legal Protection - Creditor - Fiduciary Guarantee Agreement